Repensando o design: estratégias para uma comunicação plurissensorial - Freitas, Renata Oliveira Teixeira de (2014)
This thesis can be included in the field of communication research and aims to reflect on contemporary design based on the possible contributions of the body s multisensory capacities. As the mediator between the informational codes of culture and man s perceptive and cognitive mechanisms, the design activity exerts an undeniable influence and impact on the construction of society. As part of a hyperconnected context, nourished by culture and by the tools of the new media and technologies, design deals with new creation, production, integration and value generation dynamics, as well as the new demands and urgencies of social and environmental co-existence, which require new project approaches. In these terms, multisensory analysis can contribute valuable tools for research development and design practice. The working methodology consisted of mapping out projects from different knowledge domains, such as art, medicine, engineering, technology, business and design itself, in an attempt to understand the distinct forms of action and exploration of the body s sensory communication. This research was undertaken based on theories that dialog with the critique of creation processes of Salles (2006), the questions of signs and the meaning of the semiotic base of Sebeok (1991) and Colapietro (2003), and with the complexity studies of Morin (2005). The discussions relating to communication systems and the contemporary market are supported by Shirky (2010), Lazzarato and Negri (2001), and Rifkin (2014). As far as the cognitive studies and theories of the body are concerned, the works of Nicolelis (2011) and Greiner (2005, 2010) were consulted. When referring to the design and innovation area, we turned to Manzini (2008), Margolin and Buchanan (1995), Brown (2010), Bonsiepe (2011ab), and Thackara (2008). The results of this research showed that knowledge of and investigation into these potentialities can supply project activation strategies, creative resources and means of interaction between people and products, spaces and services, contributing towards a projective action, that is more innovative, sustainable and coherent with the urgencies of the historical and cultural context, as well as promoting positive impacts on the systemic progression scale